2020
DOI: 10.3389/fendo.2020.572384
|View full text |Cite
|
Sign up to set email alerts
|

Serum Trace Elements in Patients With Polycystic Ovary Syndrome: A Systematic Review and Meta-Analysis

Abstract: Polycystic ovary syndrome (PCOS) is reported to be associated with certain trace elements. However, previous data are inconsistent and potentially biased due to small sample sizes. The potential utility of trace element levels for screening of PCOS remains to be established. The aim of this meta-analysis was to investigate the potential relationships between PCOS and serum levels of zinc (Zn), copper (Cu), magnesium (Mg), iron (Fe) and ferritin. We carried out a literature search of PubMed, EMBASE, and Web of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 53 publications
1
24
0
Order By: Relevance
“…Wu et al revealed that TFRC induces cysteine deprivation and regulates system Xc − , which transports extracellular cystine to cytoplasm for the exchange of intracellular glutamate [ 10 ]. Iron metabolisms collectively participate in endocrine disorders, including diabetes [ 12 ], thalassemia [ 13 ], cervical cancer [ 14 ], and PCOS [ 15 , 16 ]. However, the underlying mechanisms are still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Wu et al revealed that TFRC induces cysteine deprivation and regulates system Xc − , which transports extracellular cystine to cytoplasm for the exchange of intracellular glutamate [ 10 ]. Iron metabolisms collectively participate in endocrine disorders, including diabetes [ 12 ], thalassemia [ 13 ], cervical cancer [ 14 ], and PCOS [ 15 , 16 ]. However, the underlying mechanisms are still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent systematic review and meta-analysis, Yin et al showed that the serum Zn concentration was lower in polycystic ovary syndrome (PCOS) women with IR than in healthy women. However, there was no significant difference in serum Zn concentration when compared between healthy control and PCOS women without IR (34).…”
Section: Discussionmentioning
confidence: 69%
“…The process of cell death is usually characterized by a large amount of iron accumulation and lipid peroxidation (32). Iron metabolism is involved in endocrine diseases, including PCOS (33,34), while its underlying mechanism remains unclear. SLC7A11, the cystine/glutamate antiporter, functions to transport cysteine for glutathione synthesis and antioxidation, which is an upstream regulator of the ferroptosis pathway and can inhibit ferroptosis when its expression is upregulated (35).…”
Section: Discussionmentioning
confidence: 99%